High‐resolution ice‐core analyses identify the Eldgjá eruption and a cluster of Icelandic and trans‐continental tephras between 936 and 943 CE - Hutchison, William; Gabriel, Imogen; Plunkett, Gill; Burke, Andrea; Sugden, Patrick; Innes, Helen; Davies, Siwan; Moreland, William M.; Krüger, Kirstin; Wilson, Rob; Vinther, Bo M.; Dahl-Jensen, Dorthe; et al. (Journal of Geophysical Research: Atmospheres, 2024)
The Eldgjá eruption is the largest basalt lava flood of the Common Era. It has been linked to a major ice-core sulfur (S) spike in 939–940 CE and Northern Hemisphere summer cooling in 940 CE. Despite its magnitude and potential climate impacts, uncertainties remain concerning the eruption timeline, atmospheric dispersal of emitted volatiles, and coincident volcanism in Iceland and elsewhere. Here, we present a comprehensive analysis of Greenland ice-cores from 936 to 943 CE, revealing a complex volatile record and cryptotephra with numerous geochemical populations. Transitional alkali basalt tephra matching Eldgjá are found in 939–940 CE, while tholeiitic basalt shards present in 936/937 CE and 940/941 CE are compatible with contemporaneous Icelandic eruptions from Grímsvötn and Bárðarbunga-Veiðivötn systems (including V-Sv tephra). We also find four silicic tephra populations, one of which we link to the Jala Pumice of Ceboruco (Mexico) at 941 ± 1 CE. Triple S isotopes, Δ33S, spanning 936–940 CE are indicative of upper tropospheric/lower stratospheric transport of aerosol sourced from the Icelandic fissure eruptions. However, anomalous Δ33S (down to −0.4‰) in 940–941 CE evidence stratospheric aerosol transport consistent with summer surface cooling revealed by tree-ring reconstructions. Tephra associated with the anomalous Δ33S have a variety of compositions, complicating the attribution of climate cooling to Eldgjá alone. Nevertheless, our study confirms a major S emission from Eldgjá in 939–940 CE and implicates Eldgjá and a cluster of eruptions as triggers of summer cooling, severe winters, and privations in ∼940 CE.